2016
DOI: 10.4238/gmr.15027807
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated microRNA-301a in osteosarcoma promotes tumor progression by targeting CDC14A

Abstract: ABSTRACT. MicroRNAs (miRs) are associated with tumor progression in various cancers, such as gastric and hepatic carcinomas, and lung cancer. miR-301a is overexpressed and displays oncogenic activity in cancers. We investigated the biological involvement of miR301a in osteosarcoma (OS). Quantitative real-time polymerase chain reaction (qRT-PCR) was used to analyze expression levels of miR-301a in 24 OS and matched adjacent non-tumor tissues. A miR-301a mimic was transferred into OS cell lines U-2 OS and MG-63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Certain microRNAs can promote the tumorigenesis of osteosarcoma. Ni et al ( 11 ) found that miR-301a is frequently upregulated in osteosarcoma and that aberrant expression of miR-301a promotes the proliferation of osteosarcoma cell lines. miR-17-5p has also shown diagnostic and prognostic significance in osteosarcoma, as the overexpression of miR-17-5p substantially promotes malignant phenotypes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain microRNAs can promote the tumorigenesis of osteosarcoma. Ni et al ( 11 ) found that miR-301a is frequently upregulated in osteosarcoma and that aberrant expression of miR-301a promotes the proliferation of osteosarcoma cell lines. miR-17-5p has also shown diagnostic and prognostic significance in osteosarcoma, as the overexpression of miR-17-5p substantially promotes malignant phenotypes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although AML is a relatively rare disease, accounting for ~1.2% of cases of cancer-associated mortality, its incidence is expected to increase as the population ages (20). Several miRNAs are located inside or close to chromosomal fragile sites, which are frequently lost or amplified in cancer, and the correlation between miRNAs and cancer has become a focus for the diagnosis and therapy of cancer (21,22). In the present study, it was demonstrated that the expression of miR-21 was significantly increased in peripheral blood monocytes of patients with AML, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fenger et al investigated on miR-9 in OS, Ni et al showed not only that miR-301a is overexpressed in OS cell lines but also that this miRNA enhances cell migration and inhibits apoptosis [ 192 ]. Therefore, they confirmed the carcinogenic function of miR-301a in OS, which was only observed in others cancers [ 193 , 194 ].…”
Section: Mirnas and Primary Bone Tumoursmentioning
confidence: 99%